Cement-treated soil blocks with vegetative faces - JUSTINIANO HENRY G (2013)
A retaining wall or steeply faced slope is disclosed having a naturally green facade. The wall or slope is made of blocks of compacted earth, each having a face reinforced with wire mesh and covered with vegetation such as native grasses. The blocks may be formed onsite, saving transportation costs and other waste, using native soils. The mesh may extend beyond other faces of each block to provide handles and geogrid anchoring. A press is disclosed to form the blocks by compacting soil mixed with cement, the press including hydraulic rams or screw jacks that create immense pressures and having wedge shaped sides that relieve lateral confining pressure when the block is extracted.